2019
DOI: 10.1186/s40795-019-0274-y
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of minimum acceptable diet among children aged 6–23 months in orthodox religion followers during fasting season in rural area, DEMBECHA, north West Ethiopia

Abstract: Background: Under-nutrition is the cause for poor physical and mental development and has more burden among infants and young children aged between 6 and 23 months. Cultural practices like not providing animal source foods for infants and young child aged between 6 and 23 months were barrier for practicing proper children feeding. The aim of this study was to assess minimum acceptable diet and associated factors among children aged between 6 and 23 months in Orthodox religion during fasting season in rural are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
64
6
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 19 publications
16
64
6
3
Order By: Relevance
“…Among a sample of children from South West Ethiopia, Edris et al found 38% of the children attaining minimum diet diversity score [21]. The ndings of this study are however comparable to the 8.6% of children aged 6-23 months meeting minimum acceptable diet reported among children from a rural area in North West Ethiopia [13] and the 36.7% and 7.3% rates of minimum meal frequency and minimum adequate diet respectively reported among children from the Cross-River State of Nigeria [12]. Our ndings also compare favourably with the 12% of Ghanaian children meeting minimum adequate diet as reported in the 2017/2018 Multiple Indicator Cluster Survey report for Ghana [22].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Among a sample of children from South West Ethiopia, Edris et al found 38% of the children attaining minimum diet diversity score [21]. The ndings of this study are however comparable to the 8.6% of children aged 6-23 months meeting minimum acceptable diet reported among children from a rural area in North West Ethiopia [13] and the 36.7% and 7.3% rates of minimum meal frequency and minimum adequate diet respectively reported among children from the Cross-River State of Nigeria [12]. Our ndings also compare favourably with the 12% of Ghanaian children meeting minimum adequate diet as reported in the 2017/2018 Multiple Indicator Cluster Survey report for Ghana [22].…”
Section: Discussionsupporting
confidence: 55%
“…In Nigeria, Udoh et al [12]found 31.5% of a sample of 330 children aged 6-23 months from Cross River State meeting minimum diet diversity, 36.5% minimum meal frequency and 7.3% received an acceptable diet. A community-based cross-sectional study among a sample of 506 children from North West Ethiopia found only 63% of the children receiving minimum meal frequency, 9.8% for minimum diet diversity and only 8.6% received the minimum acceptable diet [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,11,13,18 A study by Mulat E. et al report even less frequency of MAD in west Ethiopia. 21 Higher education status of the mother was found to be a significantly associated with higher MAD, as also reported by Mulat E et al 21 The study was conducted in a single urban slum of Delhi and therefore its external validity is limited. The association between the complementary feeding indicators and certain socio-demographic indicators is exploratory as the sample sizes and study design was primarily for a descriptive study and not a comparative study.…”
Section: Discussionmentioning
confidence: 57%
“…A number of factors have been noted for the less optimal rates of appropriate complementary feeding including maternal education, income levels, antenatal attendance, spouse employment status, quality of institutional healthcare delivery, women empowerment in decision making, and among others [11,[13][14][15]. Notable among these factors is the mothers' knowledge and attitudes towards recommended infant and young child feeding practices.…”
Section: Introductionmentioning
confidence: 99%